KUALITAS PELAYANAN PENDIDIKAN PADA STMA TRISAKTI DENGAN MENGGUNAKAN METODE EDUQUAL DAN IMPORTANCE PERFORMANCE ANALYSIS (IPA) - Wahyuari, Wahyuari; Syahrial Sidik; Alvernia Kurniartha; Bunga Kalista (Journal of Innovation Research and Knowledge, 2025)
This study aims to analyze the quality of educational services at STMA Trisakti by integrating the EduQual and Importance Performance Analysis (IPA) methods. EduQual is used to measure service quality based on five main dimensions: learning outcomes, responsiveness, physical facilities, personal development, and academics. Meanwhile, IPA is applied to map the gap between actual performance and student expectations, as well as to determine service improvement priorities. Data was collected through a questionnaire from 119 active students representing various programs of study and educational levels. The analysis results indicate that all service dimensions have negative GAP values, indicating that performance has not fully met student expectations. The dimensions with the largest GAPs were physical facilities and academic service responsiveness. IPA analysis reinforced these findings, prioritizing academic service responsiveness indicators as the top priority for improvement. This study contributes theoretically to the development of a service quality evaluation model based on a combination of EduQual and IPA, and practically provides strategic recommendations to STMA Trisakti for improving service quality and student satisfaction sustainably.